2014
DOI: 10.1111/mms.12112
|View full text |Cite
|
Sign up to set email alerts
|

Do man‐made structures and water depth affect the diel rhythms in click recordings of harbor porpoises (Phocoena phocoena)?

Abstract: The construction of industrial offshore structures may lead to colonization by a variety of marine organisms resulting in locally enhanced biodiversity and biomass, which may then affect the habitat use and behavior of marine predators. For harbor porpoises high nocturnal echolocation activity was demonstrated near industrial structures and it was hypothesized that this was caused by increased feeding opportunities at night. Here we tested the hypothesis that bridge pillars will lead to more nocturnal echoloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
4
16
0
Order By: Relevance
“…Significant diurnal variation within both dolphin detections and vessel presence was observed within the current study, with more dolphin occurrences during the night and a higher vessel presence during the day. This diel pattern in dolphin activity has also been seen in a wide range of odontocetes (Goold 2000, Carlstr€ om 2005, Todd et al 2009, Soldevilla et al 2010, Leeney et al 2011, Hodge et al 2013, Linnenschmidt et al 2013, Mikkelsen et al 2013, Brandt et al 2014, Baumann-Pickering et al 2015, Lin et al 2015, Yamamoto et al 2016, including the Indo-Pacific humpback dolphin (Wang et al 2015b). Indo-Pacific humpback dolphins have also shown increases in the acoustic activity associated with feeding during nights compared to day periods (Wang et al 2015b).…”
Section: Discussionmentioning
confidence: 54%
“…Significant diurnal variation within both dolphin detections and vessel presence was observed within the current study, with more dolphin occurrences during the night and a higher vessel presence during the day. This diel pattern in dolphin activity has also been seen in a wide range of odontocetes (Goold 2000, Carlstr€ om 2005, Todd et al 2009, Soldevilla et al 2010, Leeney et al 2011, Hodge et al 2013, Linnenschmidt et al 2013, Mikkelsen et al 2013, Brandt et al 2014, Baumann-Pickering et al 2015, Lin et al 2015, Yamamoto et al 2016, including the Indo-Pacific humpback dolphin (Wang et al 2015b). Indo-Pacific humpback dolphins have also shown increases in the acoustic activity associated with feeding during nights compared to day periods (Wang et al 2015b).…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, water depth has a significant impact on porpoise diel rhythms, with more nocturnal porpoise echolocation activity occurring in deeper waters (Brandt et al . , Wisniewska et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…This is concurrent with other PAM studies that reported porpoises appear to shift their distribution to different depths and/or habitats at night, perhaps to take advantage of changing prey availability (Carlström 2005, Todd et al 2009, Mikkelsen et al 2013). Furthermore, water depth has a significant impact on porpoise diel rhythms, with more nocturnal porpoise echolocation activity occurring in deeper waters (Brandt et al 2014, Wisniewska et al 2016. In deeper waters, porpoises may be feeding pelagically on prey species that vertically migrate up into the water column at night, such as herring (Cardinale et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…), which are all known prey species for the marine mammal species observed during this reporting programme (Thompson et al, 1996;Abend & Smith, 1997;Pauly et al, 1998;Olsen & Holst, 2001;Sveegaard et al, 2012). Similarly, increased availability of prey items are associated with presence of top predators around a wide range of marine structures such as a reconstructed stony reef (Mikkelsen et al, 2013), a large bridge (Brandt et al, 2014), O&G facilities (Todd et al, 2009Arnould et al, 2015), and wind farms (Russell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%